Sensor location in feedback control of partial differential equation systems - Faulds, A.L.; King, B.B. (2000 IEEE International Conference on Control Applications, 2000)
The task of placing sensors for purposes of feedback control is vital in order to obtain information necessary for accurate state estimation. We present a method for optimal location of sensors which is motivated by the feedback control law for the distributed parameter system. In particular, we show how feedback functional gains reflect spatial regions over which accurate information is paramount for control. We use this information in an algorithm which computes centroidal Voronoi tesselations, yielding optimal locations for sensors. This placement is compared with three others to show that location can be more important than number of sensors.